2010
DOI: 10.1371/journal.pcbi.1000751
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate Dependence of Variability Analysis

Abstract: Analysis of motor performance variability in tasks with redundancy affords insight about synergies underlying central nervous system (CNS) control. Preferential distribution of variability in ways that minimally affect task performance suggests sophisticated neural control. Unfortunately, in the analysis of variability the choice of coordinates used to represent multi-dimensional data may profoundly affect analysis, introducing an arbitrariness which compromises its conclusions. This paper assesses the influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 41 publications
4
66
0
Order By: Relevance
“…Recently, Sternad et al [29] demonstrated that the UCM analysis is sensitive to the choice of the coordinates that are used to define the task related and unrelated manifolds. An elegant solution to this problem was recently proposed [30], but it was only applied to static tasks to date.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Sternad et al [29] demonstrated that the UCM analysis is sensitive to the choice of the coordinates that are used to define the task related and unrelated manifolds. An elegant solution to this problem was recently proposed [30], but it was only applied to static tasks to date.…”
Section: Introductionmentioning
confidence: 99%
“…Although commonly employed in robotics, such decoupling is a limiting factor to encode gestures and sensorimotor streams, because it does not fully exploit principles underlying coordination, synergies and actionperception couplings [39], [40], [41].…”
Section: N N=1mentioning
confidence: 99%
“…In the case of human movements, it has been shown that redundancy provides a way to cope with noise at a motor level by channeling it in directions that have minimal effect on achieving the task goal [39]. Skilled performers can take advantage of this redundancy and align their actions with the solution manifold corresponding to a given task goal, i.e., the space in which noise and variability have little or no effect on the end result.…”
Section: Exploitation Of Covariance Information In Rlmentioning
confidence: 99%
“…We take inspiration from the proposal addressed in [39] that variability may offer a way to quantify error tolerance via the shape of the result function. Indeed, one obvious reason to prefer some locations over others in the policy parameters space is the sensitivity of the result to variability (tolerance to errors).…”
Section: Exploitation Of Covariance Information In Rlmentioning
confidence: 99%
See 1 more Smart Citation